2013
DOI: 10.1111/iej.12125
|View full text |Cite
|
Sign up to set email alerts
|

Influence of refreshment/activation cycles and temperature rise on the reaction rate of sodium hypochlorite with bovine dentine during ultrasonic activated irrigation

Abstract: The reaction rate of NaOCl with dentine is enhanced by refreshment, ultrasonic activation and exposure time. Temperature rise of irrigant during ultrasonic activation was not sufficient to alter the reaction rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 34 publications
3
31
2
2
Order By: Relevance
“…Mechanical effects, such as acoustic streaming and cavitation, are dominant factors in ultrasonic‐activated irrigation. Moreover, ultrasonic activation could cause decomposition of the molecule and degassing of the solution, even if these mechanisms seem to have no effects on the increase of chemical efficiency (reaction rate) of NaOCl …”
Section: Discussionmentioning
confidence: 99%
“…Mechanical effects, such as acoustic streaming and cavitation, are dominant factors in ultrasonic‐activated irrigation. Moreover, ultrasonic activation could cause decomposition of the molecule and degassing of the solution, even if these mechanisms seem to have no effects on the increase of chemical efficiency (reaction rate) of NaOCl …”
Section: Discussionmentioning
confidence: 99%
“…These variables are found to be associated with mental distress in other studies [8,15], and should be adjusted for.…”
Section: Methodsmentioning
confidence: 99%
“…In our study, the total irrigation times were limited at 40 s for each irrigation solution and irrigation-activation cycles were applied with a standardized protocol using a 5-s rest time in all root canals, according to previous investigation [30]. This timing protocol can help to prevent severe peritubular erosion [31], as well as the possible hazardous effects of temperature rise on the dentine surface, depending on the use of ultrasonics and lasers in the root canal [30,32]. Moreover, previous studies [4,6,33] have reported that NaOCl irrigation had an adverse effect on adhesion at the resin cement-dentine interface.…”
Section: Discussionmentioning
confidence: 99%